Manufacturers' Warranties of Consumer Goods - Curtis R. Reitz (Washington University Law Quarterly, 1997)
The market background for this Article is the matter of the warranties that manufacturers of consumer goods make to those who buy those goods from retail dealers. Is this a matter on which UCC Article 2 can be useful in facilitating the achievement of objectives that are common to consumers and manufacturers? Is this a matter on which assessment of the existing balance of the interests of consumers and manufacturers requires intervention by Article 2 to improve the position of consumers? These questions are high on the agenda of those currently engaged in revision of Article 2.
Keywords: Consumer protection; Warranty